Evaluation of morphometric parameters to determine hydrological behaviours of the lower Tel sub-basin, India - Mamina Behera; Ashis Chandra Pathy (National Geographical Journal of India, 2025)
Geospatial technology serves as a critical modern tool for morphometric analysis of river basins. By integrating satellite imagery from remote sensing with Geographic Information Systems (GIS), it is now possible to accurately assess the morphometry of river basins. The present objective is to determine the morphometry of the lower Tel sub-basin to understand the physical terrain and water flow dynamics. SRTM DEM data were utilized in the ArcGIS platform to delineate the drainage boundary and the stream network of the sub-basin. Various parameters of morphometric assessment including linear, areal, and relief aspects were evaluated for the sub-basin. The results show that the Lower Tel sub-basin spans an area of approximately 9,048 square kilometers and includes stream orders up to the sixth order, with a total of 796 stream segments. The bifurcation ratio suggests minimal structural interference in the sub-basin. Based on the shape factor, the sub-basin possesses an elongated shape. The existence of hard-resistant bedrock in the sub-basin was suggested by lower drainage density value, which led to lower permeability and high surface runoff. The drainage texture is coarse implying less terrain dissection. The length of overland flow, i.e., 1.27 km, suggests low relief, low infiltration, and a longer flow path. The relief aspect suggests the sub-basins that the sub-basin has low relief and a gentle slope. Hence, it concludes that the geospatial technique is very useful to get a detailed understanding of drain basin hydrology. These findings are extremely useful for basin water management, conservation policies, and sustainable development planning for the basin.